EFEKTIFITAS PEMBELAJARAN MATEMATIKA HUMANISTIK BERBASIS KONSTRUKTIVISME BERBANTUAN E-LEARNING MATERI SEGI TIGA PADA KELAS 7 SMP N 2 LIMPUNG TAHUN AKADEMIK 2009/2010 - Muhammad Prayitno (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
This  research  is  based  on  the  use  of  ineffective  learning  models  which  haven’t based  on  the  humanistic  values  and  the  lack  of  constructivism  in  compounding  the students’  knowledge so  that  the  students’  achievement  is  disappointed and  the  negative view of the students in learning math. This is an experimental research, and the research question is that will the constructivism based humanistic mathematic by e- learning of the triangle  course  of  the  seventh  grade  be  effective?  The  active  skill  process  is  as  the independent variable and the learning achievement is as the dependant variable. The data is  found  out  by  learning  achievement  test  and  question  sheets.  The  research  method  is descriptive,  the  analysis  of  the  sample  t  test and  regression.  The  influence  test  is  by  a simultaneous study to find out the learning achievement, the influence of activeness to the learning  achievement  and  the  difference  between  the  control  classes  to  the  experiment class.The  result  of  the  research  is  that  the  learning  is  effective, signed  by  3  indicators, they are; (1) the students’ achievement is up to the classical achievement 69,28 more than KKM 60, and the individual achievement is up to 75%, (2) the activeness of the students gives  a  positive  influence  to  the  students’  achievement;  33,8%,  (3)  the  average  of  the experiment class is 69,28 better than the control class in average 63,67. Key words: the learning effectiveness, Humanistic, constructivism.